Review of Arabic Autocorrect System in Sahehly Application - Nuraisyah, Andini; Fuada, Farha; Umbar, Kisno (Institut Agama Islam Negeri Curup, 2024)
This research was conducted to investigate and determine the accuracy of the automatic correction system for Arabic texts. The focus of this research was the autocorrection system found in the Sahehly application, with analysis conducted on the harakat, tarakib, and grammatical aspects of the Arabic language. Accuracy is a very important part of an application system because accuracy can influence correct results and reduce the occurrence of errors. This study examined the review of the autocorrect system in the Sahehly application. The sample text used was the book of Fathul Qorib in the chapter of law and witnesses. The method used in this research was descriptive analysis with text study research design. From the results of the analysis, 3 words were found to be corrected with the application of Sahehly on grammatical aspects. However, when reviewed, the results of the Sahehly correction were less precise, and no changes needed to be made because they were correct. Then, the researchers found inaccuracies in 22 words that were given harakat by the Sahehly application. Thus, the presence of Sahehly is one of the developments of artificial intelligence (AI) in Arabic to provide harakat, but it is not fully perfect. Therefore, the use of Sahehly should be re-examined by referring to the knowledge that has been learned and referring to the available Arabic dictionaries and books.